Medicina interna pediátrica: abordaje y manejo clínico del paciente pediátrico en la internación - Alejandro Pace (Revista del Hospital Italiano de Buenos Aires)
Pediatric Internal Medicine combines a vast and outstanding selection of contents chosen according to frequency, relevance, and complexity with comprehensive, safe, and quality pediatric care in terms of technical, scientific, and human aspects addressed to pediatricians in hospitalization, pediatric sub-specialists, pediatricians in training and medical students.